Studi Proses Difusi melalui Membran dengan Pendekatan Kompartemen: Fransiska Retno Kuntari, Susatyo Pranoto, Adita Sutresno - Fransiska Retno Kuntari Fransiska Retno Kuntari; Susatyo Pranoto Susatyo Pranoto; Adita Sutresno Adita Sutresno (Jurnal Fisika dan Aplikasinya, 2019)
Diffusion is an important process in daily life, especially in the system of the human body. In this study, the diffusion process in human body system was studied using the compartments approach. The purpose of this study is to examine the effect of channel area, concentration, and diffusion coefficient on the rate of diffusion. Two compartments each sized were separated by a perforated barrier that represents areas of high and low concentrations, which were connected by a channel. Two Conductivity Probe sensors were placed in each compartment with the same distance to the barrierand were connected with a Vernier interface and a computer that hadLogger Lite 1.9.4 installed. The conductivity data is converted into concentration, then analyzed. The compartment model can be used to study diffusion process in the human body system. Diffusion rate is directly proportional to channel area, concentration and diffusion coefficient.